Atrial Fibrillation Ablation in Systolic Dysfunction: Clinical and Echocardiographic Outcomes - Lobo,Tasso Julio (2015)
Background:Heart failure and atrial fibrillation (AF) often coexist in a deleterious cycle.Objective:To evaluate the clinical and echocardiographic outcomes of patients with ventricular systolic dysfunction and AF treated with radiofrequency (RF) ablation.Methods:Patients with ventricular systolic dysfunction [ejection fraction (EF) <50%] and AF refractory to drug therapy underwent stepwise RF ablation in the same session with pulmonary vein isolation, ablation of AF nests and of residual atrial tachycardia, named "background tachycardia". Clinical (NYHA functional class) and echocardiographic (EF, left atrial diameter) data were compared (McNemar test and t test) before and after ablation.Results:31 patients (6 women, 25 men), aged 37 to 77 years (mean, 59.8±10.6), underwent RF ablation. The etiology was mainly idiopathic (19 p, 61%). During a mean follow-up of 20.3±17 months, 24 patients (77%) were in sinus rhythm, 11 (35%) being on amiodarone. Eight patients (26%) underwent more than one procedure (6 underwent 2 procedures, and 2 underwent 3 procedures). Significant NYHA functional class improvement was observed (pre-ablation: 2.23±0.56; postablation: 1.13±0.35; p<0.0001). The echocardiographic outcome also showed significant ventricular function improvement (EF pre: 44.68%±6.02%, post: 59%±13.2%, p=0.0005) and a significant left atrial diameter reduction (pre: 46.61±7.3 mm; post: 43.59±6.6 mm; p=0.026). No major complications occurred.Conclusion:Our findings suggest that AF ablation in patients with ventricular systolic dysfunction is a safe and highly effective procedure. Arrhythmia control has a great impact on ventricular function recovery and functional class improvement.